Creativity and its discontents : China's creative industries and intellectual property rights offenses - Pang, Laikwan (Online access with subscription: Duke University Press., 2012)
Laikwan Pang offers a complex critical analysis of creativity, creative industries, and the impact of Western copyright laws on creativity in China.